Phytochemical Survey and Pharmacological Activities of the Indole Alkaloids in the Genus Voacanga Thouars (Apocynaceae) – An Update - G. Macabeo, Allan Patrick; D. Alejandro, Grecebio Jonathan; Hallare, Arnold V.; Vidar, Warren S.; Villaflores, Oliver B. (Pharmacognosy Reviews)
Numerous species of the Apocynaceous genus Voacanga Thouars have been demonstrated to elaborate a host of indole alkaloids that display various structural complexities and a wide array of biological activities. Monoterpenoid indole alkaloids are nitrogenous metabolites borne from the biosynthetic union of tryptophan and the terpene-derived iridoid, secologanin. As a genus is closely related to Tabernaemontana, representative species of Voacanga were reported to contain the vobasine, vallesamine, eburnane, iboga and aspidosperma–type indole alkaloids. A lot of these compounds are associated with analgesic, CNS, antimicrobial, anti-ulcer, cytotoxic, antioxidant and antimalarial activities. Voacanga is a small taxon with 12 species that are mainly found in tropical Africa and Malesia except for V. grandifolia which extends to Australia. This comprehensive review compiles the phytochemical and pharmacological explorations that have been undertaken on Voacanga in relation to its indole alkaloids.
Keywords: Voacanga; indole alkaloids; anti-ulcer; antibacterial; cytotoxic; CNS activity